Tutela penal do meio ambiente: a responsabilidade penal das pessoas jurídicas e a teoria da dupla imputação à luz do recurso extraordinário nº 548.181/PR - Silva, Joathan Robério da (Universidade Federal Rural do Semi-Árido, 2018)
Based on a bibliographical and jurisprudential research, with an inductive method, this paper intends to analyze the jurisprudential evolution represented by RE 548.181/PR and its consequences, in the dogmatic scope, to the criminal responsibility of legal 4 entities in brazilian legal order. The judgment of the First Class of the Supreme Court has decided that the article 225, § 3 of the Federal Constitution does not require the simultaneous identification and imputation of the crime against environment to the theoretically responsable for the company. The criminal responsibility from moral entities is rejected by prevailing legal penal system dogmatics, which denies to corporations the capacity of action and guilt. Despite this, for criminal and political reasons, this capacity was recognized by the juridical systems, including the national one, and requires the reformulation of the criminal law in its categories concerning to the development of a compatible crime theory that give to the companies the nature of legal persons. The Supreme Court at first adopted the majority understanding, rejecting the possibility of a company legaly respond for a crime. After the creation of the 1988’s Federal Constitution, the Superior Court of Justice and the Supreme Court began to recognize the heterorresponsibility for the legal entity. The RE 548.181/PR represented a third hermeneutical stage, characterized by the self-responsibility of the moral entities. Despite the dual vicarious liability, it is necessary to identify the conduct of the company's internal agents to verify if the environmental crime was committed with the consent of the representative or the collegiate body, for the advantage or benefit of the entity.
Artigo Acadêmico
Keywords: Responsabilidade penal da pessoa jurídica; RE 548.181/PR; Teoria da dupla imputação; Criminal liability of legal entities; RE 548.181/PR; Dual vicarious liability; CIENCIAS SOCIAIS APLICADAS::DIREITO